2017
DOI: 10.3329/ijarit.v7i1.33315
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability, correlation and path coefficients of yield and its components analysis in pumpkin (Cucurbita moschata Duch Ex Poir)

Abstract: Genetic variability, correlation and path coefficient were studied for yield and yield component traits in twenty one diverse genotypes of pumpkin. Highest genotypic coefficient of variation was recorded for fruit length (cm), single fruit weight (kg), Brix (%) and yield per plant (kg). Heritability estimates in broad sense were higher for almost all the characters. The characters namely, fruit length, single fruit weight, yield per plant and brix% had high genotypic coefficient of variation coupled with herit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…The present study describes the evaluation of one of the largest germplasm volumes of C. moschata. The high estimates of genotypic variance for characteristics related to seed production observed in this study corroborate those reported by [51], who also observed higher…”
Section: Plos Onesupporting
confidence: 92%
“…The present study describes the evaluation of one of the largest germplasm volumes of C. moschata. The high estimates of genotypic variance for characteristics related to seed production observed in this study corroborate those reported by [51], who also observed higher…”
Section: Plos Onesupporting
confidence: 92%
“…Most of the phenotypic variance estimates of these characteristics were due to the contribution of genotypic variance. These results corroborate those reported by [46], who also observed higher estimates of genotypic variances for NSF and flowering characteristics, and also a greater contribution of genotypic variance to the phenotypic variance in these characteristics. Additionally, most of the characteristics expressed high estimates of heritability (>0.50), according to the classification of [47].…”
Section: Discussionsupporting
confidence: 92%
“…These fruit yield characters are very effective in discriminating between varieties of Cucurbita spp., and explaining variations (Norman et al, 2014); therefore, are the best suited for selection of pumpkins for germplasms and breeding programmes (Xiaohua et al, 2011;Mladenovic et al, 2014). They should also be used as priority characters in studies of morphological diversity, selection and effective utilisation of Mohsin et al (2017) observed strong associations between fruit yield characters and plant productivity of pumpkins. Yield characters are highly heritable and their expression is not easily affected by environmental factors (Martins et al, 2016;Mohsin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They should also be used as priority characters in studies of morphological diversity, selection and effective utilisation of Mohsin et al (2017) observed strong associations between fruit yield characters and plant productivity of pumpkins. Yield characters are highly heritable and their expression is not easily affected by environmental factors (Martins et al, 2016;Mohsin et al, 2017). The PCA scatter plot (Fig.…”
Section: Discussionmentioning
confidence: 99%